1986
DOI: 10.2466/pr0.1986.59.2.911
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Worldmindedness, Satisfaction, and Commitment for Hirers of Foreign Student Exchanges

Abstract: Srrmmary.-Sampsonand Smith's Worldmindedness scale is a 32-item disagree-agree inventory designed to assess worldminded values in individuals. This procedure, developed and tested in the United States, has here been applied to a Canadian sarnple of 9 1 company hirers of foreigo students and 21 company nonhirers of such. In doing so, the stability of previous findings for USA students and the reliability of the instrument have also been assessed. Also, using a series of disagree-agree anitudinal items, the hire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Post-hoc analyses showed that meaningful differences existed between all three levels of world-mindedness. Schell, Sherritt, Lewis, and Mansfield (1986) also applied Sampson and Smith's (1957) World-Mindedness Scale to a business environment. The researchers hypothesized businesses that employed foreign exchange students would have significantly higher world-mindedness scores than their non-hiring business counterparts.…”
Section: The Development Of Hett's Global-mindedness Scalementioning
confidence: 99%
“…Post-hoc analyses showed that meaningful differences existed between all three levels of world-mindedness. Schell, Sherritt, Lewis, and Mansfield (1986) also applied Sampson and Smith's (1957) World-Mindedness Scale to a business environment. The researchers hypothesized businesses that employed foreign exchange students would have significantly higher world-mindedness scores than their non-hiring business counterparts.…”
Section: The Development Of Hett's Global-mindedness Scalementioning
confidence: 99%
“…In turn, there exist several implications of world-mindedness on individuals' view of foreign cultures. According to Schell et al (1986), less world-minded personnel managers were less likely to hire foreign students. found that managers and professionals who were not interested in domestic politics were considered highly world-minded consumers.…”
Section: World-mindednessmentioning
confidence: 99%